Intra-sentence Punctuation Insertion in Natural Language Generation - Zhang, Zhu; Gamon, Michael; Corston-Oliver, Simon; Ringger, Eric (2002)
We describe a punctuation insertion model used in the sentence realization module of a natural language generation system for English and German. The model is based on a decision tree classifier that uses linguistically sophisticated features. The classifier outperforms a word n-gram model trained on the same data.